Validação do protocolo de acolhimento com classificação de risco em pediatria - Magalhães, Fernanda Jorge (2012)
Among the technologies for the nursing care we highlight the protocols, which can establish the criteria favorable clinical judgment and decision making in emergency situations and emergency. The Protocol Host with Risk Rating (ACCR) in Pediatrics aims to classify the priority of caring for children and adolescents from the risk of complications and death in emergency rooms. Had as main objective: to validate the protocol in Pediatrics ACCR to classify the priority of caring for children and adolescents in situations of urgency and emergency. Methodological study developed from the validation of appearance and content of the protocol, with the participation of nine judges. Data collection was conducted from March to July 2012, being the judges issued a letter of invitation and an instrument containing identification data, aspects of the appearance of the protocol with 6 items and aspects related to content validity divided into 14 items of general protocol and list of 72 attributes (warning signs with clinical indicators), which were evaluated for the criteria of simplicity, clarity and relevance. The concepts of warning signs, their antecedents and consequences were established from the literature review. The data were organized in tables, charts and figures, and statistically analyzed by content validity index (CVI). The project was approved by the Ethics and Research under protocol # 325/11. As a result, it was possible to define the concepts, attributes and consequences of the 30 items included in the protocol. As for validation by judges, the appearance was seen as adequate as simplicity, clarity and relevance, since there IVC above 80% in 5 of 6 items in question. As for content, it was found that the assessment of general and structural aspects of the protocol, scores a 0.837 CVI. Regarding content validity, to assess the warning signs, clinical indicators, as well as ownership and corresponding risk rating determined by the judge and the study protocol; understood up service, which were considered appropriate to those which comprise more than 80.0% concordance of judges considering simplicity, clarity and relevance. It is concluded that this protocol was considered valid as to appearance and content to determine the priority of caring for children and / or adolescents in emergency care units.